An Overview of Physical Exercise and Antioxidant Supplementation Influences on Skeletal Muscle Oxidative Stress - Shima Taherkhani; Kosar Valaei; Hamid Arazi; Katsuhiko Suzuki (MDPI AG, 2021)
One of the essential injuries caused by moderate to high-intensity and short-duration physical activities is the overproduction of reactive oxygen species (ROS), damaging various body tissues such as skeletal muscle (SM). However, ROS is easily controlled by antioxidant defense systems during low to moderate intensity and long-term exercises. In stressful situations, antioxidant supplements are recommended to prevent ROS damage. We examined the response of SM to ROS generation during exercise using an antioxidant supplement treatment strategy in this study. The findings of this review research are paradoxical due to variances in antioxidant supplements dose and duration, intensity, length, frequency, types of exercise activities, and, in general, the lack of a regular exercise and nutrition strategy. As such, further research in this area is still being felt.